Action of Justicia pectoralis Jacq. (Acanthaceae) in the treatment of respiratory tract infections: a literature review (Research, Society and Development, 2021)
For thousands of years, humanity, in order to ensure its survival, used plants in their daily lives to help cure and treat various pathologies. This integrative medical practice is known as herbal medicine and has grown over the years as a very promising complementary alternative. Several extracts have a broad spectrum of prophylactic action against various infections, such as Justicia pectoralis Jacq. (Acanthaceae) is a medicinal herb found in several countries in America, popularly known in Brazil as "chamba", "anador" or "trevo-cumaru", being widely used in the treatment of respiratory disorders such as cough, asthma, and bronchitis. Thus, the aim of this study was to conduct a literature review on the action of Justicia pectoralis in the treatment of respiratory tract infections. Initially, a search was performed for articles indexed in Lilacs, PubMed, Google Scholar, ScienceDirect, Scielo and Medline databases published between 2010 and 2020 in Portuguese, English and Spanish. Justicia pectoralis extract is active against several bacteria, including some that cause respiratory tract infections, such as Acinetobacter baumannii, Klebsiella pneumoniae and Staphylococcus aureus. 1,2 benzopyrone and 7-hydroxycoumarin are the major phytocompounds of this plant responsible for the anti-inflammatory, bronchodilator, antihistamine, and analgesic actions that contribute to the relief of symptoms of respiratory infections. Finally, since Justicia pectoralis Jacq. (Acanthaceae) is already widely used in folk medicine and important of these activities are correlated with in vitro findings, it is necessary to deepen studies that direct the future clinical use of this species.